Editorial: Education and the Quest for Educating in the Current and the Post-COVID-19 Era - Bunmi I. Omodan; Nolutho Diko (Research in Social Sciences and Technology- OpenED Network, 2021)
This special issue contains quality, well-researched, and well-argued articles towards inter/multi-disciplinary understanding of the current and future state, manner, and disposition of social, educational, environmental, humanitarian, and technological perspectives of COVID-19 pandemic. Readers, academics, practitioners and students are provided with robust knowledge on the state and status of the COVID-19 pandemic in the world from its advent in 2020, its present state and future projections. We thank all colleagues involved in the editorial and publishing process for their supports, assistance and exceptional guidance. We are bold to say that the quality involved in the publication process of RESSAT Journal is second to none. To all our authors, your quality products remain part of the historical contribution to knowledge on the COVID-19 pandemic.